Diversifikasi Produk Sebagai Upaya Peningkatan Profit Pengrajin Kayu di Desa Kemenuh Gianyar Bali Pasca Pandemi Covid-19 - Wiwin Hartanto; Luh Putu Indah Budyawati; Kristian Suhartadi Widi Nugraha; Akhmad Ryan Pratama (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2023)
ABSTRACTThe Covid-19 pandemic has hit Bali's economic sector, which depends on tourism and Small and Medium Scale Handicrafts. One of the most affected areas is Kemenuh Village in Gianyar Regency. This village was a center for wood artisans but then experienced sluggishness due to reduced sales of woodcraft products. The decline in sales of wood products was caused by the decline in people's purchasing power due to tourist restrictions due to the Covid-19 Pandemic. The latter had only displayed their products in art shop windows, resulting in a decrease in profit of up to 80% based on interviews with several art shop owners. The production of APE is adjusted to the demand for a relatively high market share, and this is because it must meet the needs of APE in 2,457 early childhood education program institutions in Bali Province. As an illustration, the number of early childhood education program institutions in Bali Province is 2,457, while in Gianyar Regency, there are 241 institutions.Keywords: art shop, ape, bali, diversification, education  ABSTRAKPandemi Covid-19 telah memukul sektor ekonomi Bali yang bergantung pada pariwisata dan Kerajinan Skala Kecil dan Menengah. Salah satu daerah yang paling terdampak adalah Desa Kemenuh di Kabupaten Gianyar. Desa ini merupakan sentra perajin kayu namun kemudian mengalami kelesuan akibat berkurangnya penjualan produk kerajinan kayu. Penurunan penjualan produk kayu disebabkan oleh turunnya daya beli masyarakat akibat pembatasan wisatawan akibat Pandemi Covid-19. Yang terakhir hanya memajang produknya di etalase art shop, sehingga terjadi penurunan keuntungan hingga 80% berdasarkan wawancara dengan beberapa pemilik art shop. Produksi APE disesuaikan dengan permintaan pangsa pasar yang relatif tinggi, karena harus memenuhi kebutuhan APE di 2.457 lembaga program PAUD di Provinsi Bali. Sebagai gambaran, jumlah lembaga program PAUD di Provinsi Bali sebanyak 2.457, sedangkan di Kabupaten Gianyar terdapat 241 lembaga.Kata Kunci: artshop, ape, bali, diversifikasi, pendidikan